Fish toxicity testing for identification of thyroid disrupting chemicals. (1st September 2021) - Dang, ZhiChao; Arena, Maria; Kienzler, Aude
Abstract: Identification of thyroid disrupting chemicals (TDCs), one of the most studied types of endocrine disruptors (EDs), is required according to EU regulations on industrial chemicals, pesticides, and biocides. Following that requirement, the use of fish as a unique non-mammalian model species for identification of EDs may be warranted. This study summarized and evaluated effects of TDCs on fish thyroid sensitive endpoints including thyroid hormones, thyroid related gene expression, immunostaining for thyroid follicles, eye size and pigmentation, swim bladder inflation as well as effects of TDCs on secondary sex characteristics, sex ratio, growth and reproduction. Changes in thyroid sensitive endpoints may reflect the balanced outcome of different processes of the thyroid cascade. Thyroid sensitive endpoints may also be altered by non-thyroid molecular or endocrine pathways as well as non-specific factors such as general toxicity, development, stress, nutrient, and the environmental factors like temperature and pH. Defining chemical specific effects on thyroid sensitive endpoints is important for identification of TDCs. Application of the AOP (adverse outcome pathway) concept could be helpful for defining critical events needed for testing and identification of TDCs in fish. Highlights: Thyroid sensitive endpoints are influenced by thyroid disrupting chemicals (TDCs). They may also be influenced by non-thyroid pathways and non-specific factors. Defining chemical specific effects is important for TDC testing and identification.